Digital Expectations and Experiences in Education 2016
DOI: 10.1007/978-94-6300-648-4_11
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cyberbullying and Cyber Harassment on Academic Achievement

Abstract: Cyberbullying is commonly measured by either an inventory of manifest variables (i.e. cyber harassment) or the use of global items covering cyberbullying in general. This study aimed to compare these two approaches in terms of how they predict academic achievement. Structural equation modelling (SEM) was used to build recursive models including variables of academic achievement, traditional and cyber harassment, cyberbullying, socio-economic status, perceived quality of life at school, and sex. Our findings re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Emotional skills help students to feel a greater level of empathy toward their classmates, which may significantly reduce their involvement in intimidating behavior; however, one of the characteristics that is typically mentioned by cyberbullies is a low level of empathy with victims, since they do not appear to demonstrate unrest or guilt as a result of their aggressions, being unable to empathize with the victim's emotions or feelings (Hinduja and Patchin, 2007;Aricak, 2009). On the other hand, bullies tend to display poor academic performance, with low integration in academic and scholastic dynamics (Egeberg et al, 2016). So, having a positive academic adjustment (motivation for completing academic requirements, making an effort academically and satisfaction with the academic environment) acts as a protective factor against engaging in aggressive behavior toward peers.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional skills help students to feel a greater level of empathy toward their classmates, which may significantly reduce their involvement in intimidating behavior; however, one of the characteristics that is typically mentioned by cyberbullies is a low level of empathy with victims, since they do not appear to demonstrate unrest or guilt as a result of their aggressions, being unable to empathize with the victim's emotions or feelings (Hinduja and Patchin, 2007;Aricak, 2009). On the other hand, bullies tend to display poor academic performance, with low integration in academic and scholastic dynamics (Egeberg et al, 2016). So, having a positive academic adjustment (motivation for completing academic requirements, making an effort academically and satisfaction with the academic environment) acts as a protective factor against engaging in aggressive behavior toward peers.…”
Section: Discussionmentioning
confidence: 99%
“…The part that we present here is situated in the analysis of the positive relations between students and the rest of the educational community as a protection factor preventing relational or indirect bullying and cyberbullying, the two types of school harassment with the greatest prevalence in our sample. We share the vision of Giménez, Arnáiz, Cerezo, and Prodócimo (2018) that bullying is a topic of great educational and social occupation (Egeberg, Thorvaldsen, & Ronning, 2016;González-Calatayud, 2018) and that it is, therefore, important to start CONTACT Alejandra Cortés-Pascual alcortes@unizar.es from the voices of the people involved (Cano & Cortés, 2018) to determine how the subject can be studied from a positive and preventive approach. In this work we have based on two models: Bronfenbrenner's (1979) ecological model that collects the theoretical systemic vision that we want to give to the subject, and, linked to it, the Rawlings's model (2015) on school connectedness as a preventive factor for bullying behaviours.…”
Section: Introductionmentioning
confidence: 93%
“…Some results from the first year of the study are recently reported in Thorvaldsen et al (2016), and in Egeberg et al (2016). It was found that, compared to traditional bullying, cyberbullying is less common, but it now affects some 3.5% of pupils, i.e.…”
Section: Long-term Studymentioning
confidence: 99%
“…Both bullying and victimization are associated with the experience of poor quality of life (Thorvaldsen et al 2016). Quality of life is the individual's experience of life being satisfactory.…”
Section: Quality Of Lifementioning
confidence: 99%